MANEUVERING DIGITAL FRONTIER: TRANSFORMING CONSUMERS PURCHASE INTENTIONS FOR FRESH VEGETABLES THROUGH MOBILE TECHNOLOGY ADOPTION - Manan Aslam; Zhiwen Li (Journal of Animal and Plant Sciences, 2025)
This research investigates the drivers influencing consumers' intentions to purchase fresh vegetables through mobile technology, with a focus on information and communication technologies (ICTs) adoption, particularly smartphones. The integration of mobile technology into digital agribusiness practices may reduce the reliance on intermediaries in the fresh vegetable supply chain, benefiting consumers, farmers, and agribusinesses. By providing access to real-time agricultural market information, such as prices and market trends, mobile technology empowers consumers to make informed purchasing decisions. The research, based on a sample of 300 respondents from Lahore and Multan (Punjab, Pakistan), uses the well-known theories of technology adoption. to identify key drivers of consumer behavior. Findings indicate that consumer income, education level, distance to fresh vegetable markets, perceived relative advantage, compatibility, complexity, observability of technology, data security concerns, and social influence all significantly impact purchase intentions. The study highlights the need for policymakers, technology providers, and agribusinesses to promote mobile technology adoption in the fresh vegetable sector to enhance consumer satisfaction and subjective well-being, while also contributing to supply chain modernization.
Keywords: ICTs; digital agribusiness; consumer behavior; data security; supply chain modernization